The Adaptation of Building Information Modelling (BIM) on Existing Ibu Pejabat Daerah (IPD) Pasir Mas As-built Plan for Future Engineering Reference - Mohamad, Mazlan; Zakaria, Muhammad Nizam; Abd Manaf, Mohd Shahrulmizi (Recent Trends in Civil Engineering and Built Environment, 2023)
Building Information Modeling (BIM) is a modern construction method that has largely replaced conventional methods. BIM is a collaborative tool utilized by the architectural, engineering, and construction (AEC) industries that is based on multiple software solutions. For the time being, the majority of BIM processes are geared toward new construction. As a result, most existing structures will be difficult to refer to in the future. The purpose of this study is to develop a more efficient method for engineers to obtain all of the information they require for future building maintenance and operations. As a result, the existing "Blok F - Surau" building in Ibu Pejabat Daerah (IPD) Pasir Mas was analysed and designed in order to collect information on the materials employed in the construction.